Home - Blunt, Alison. (London ; New York)
1 online resource (xvi, 304 pages)
Keywords: 'Home' is a significant geographical and social concept. It is not only a three-dimensional structure, a shelter, but it is also a matrix of social relations and has wide symbolic and ideological meanings. An essential guide to studying home and domesticity, this book locates 'home' within wider traditions of thought across the social sciences and humanities. It analyzes different sources, methods and examples in both historical and contemporary contexts; ranging from homes on the American frontier and imperial domesticity in British India, to Australian suburbs, multicultural London, and South Asian diasporic homes. The core argument of the book has three main parts that cut across each of its chapters: Home-making * identity and belonging * homely and unhomely spaces. Each chapter includes text boxes and exercises and is well illustrated with cartoons, line drawings, and photographs. Readership: Outlining the social relations shaping (and being influenced by) the geographies of home, and the imaginative as well as material importance of home, this book will be a valuable reference for students of geography, sociology, gender studies, and those interested in the home and domesticity--Publisher's blurb.